An assessment of the scientific status of anthroposophic medicine, applying criteria from the philosophy of science. (October 2018) - Baars, Erik W.; Kiene, Helmut; Kienle, Gunver S.; Heusser, Peter; Hamre, Harald J.
Highlights: To our knowledge this is the first philosophical analysis of a whole medical system, using criteria from contemporary philosophy of science. Assessing the scientific status of anthroposophic medicine (AM) according to 11 criteria, all criteria were fulfilled by AM. A crucial assessment issue is: Do holistic formative forces exist, as assumed in AM, and if so, can they be empirically and rationally assessed? Future research should focus on the tenability of the ontological reductionist position in science and on the further validation of AM non-reductionist holistic concepts, methods and practices. Abstract: Objectives: The objective was to evaluate the scientific status of anthroposophic medicine (AM) according to demarcation criteria proposed in contemporary philosophy of science. Design: Criteria for what is science were retrieved from eight publications in the philosophy of science, focusing either on science in medicine or on the demarcation between science and pseudoscience or non-science. Criteria were combined, redundancies were excluded, and the final set of criteria was ordered in a logical sequence. The analysis yielded 11 demarcation criteria (community, domain, problems, goals, axiomatic basis, conceptual basis, quality of concepts, methodology, deontic basis, research products, tradition). Results: Assessing the scientific status of AM according to the 11 criteria, all criteria were fulfilled by AM. Discussion: AM is grounded on the notion that specific non-atomistic holistic formative forces exist and can be empirically and rationally assessed. From a position claiming that such holistic forces cannot possibly exist or cannot be empirically and rationally assessed, the axiomatic and conceptual basis of AM can be contested. However, such an a priori rejection is problematic in the presence of empirical evidence supporting the validity of holistic concepts, as discussed in the paper. Future research should therefore focus on the tenability of the ontological reductionist position in science and on the further validation of AM non-atomistic holistic concepts, methods and practices. Conclusion: In this analysis, using criteria from philosophy of science, AM fulfilled all 11 criteria for what is science.